2014
DOI: 10.1371/journal.pone.0115379
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cycling Cell Numbers and Stem Cell Associated Proteins as Potential Biomarkers for High Grade Human Papillomavirus+ve Pre-Neoplastic Cervical Disease

Abstract: High risk (oncogenic) human papillomavirus (HPV) infection causes cervical cancer. Infections are common but most clear naturally. Persistent infection can progress to cancer. Pre-neoplastic disease (cervical intraepithelial neoplasia/CIN) is classified by histology (CIN1-3) according to severity. Cervical abnormalities are screened for by cytology and/or detection of high risk HPV but both methods are imperfect for prediction of which women need treatment. There is a need to understand the host virus interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
0
15
0
1
Order By: Relevance
“…The use of cervical-vaginal fluid samples has demonstrated benefits as a biomarker source for lower female reproductive system pathologies, due to easy collection, with the prospective of utilizing self-tests. The following detection methods have been used, to date, for this sample examination: RT-qPCR for mRNA, flow cytometry and antibody-based proteomic microarray for stem cell-associated genes and flow cytometry for increased cell proliferation ( 121 ).…”
Section: Proteomics Technologies For the Identification Of Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of cervical-vaginal fluid samples has demonstrated benefits as a biomarker source for lower female reproductive system pathologies, due to easy collection, with the prospective of utilizing self-tests. The following detection methods have been used, to date, for this sample examination: RT-qPCR for mRNA, flow cytometry and antibody-based proteomic microarray for stem cell-associated genes and flow cytometry for increased cell proliferation ( 121 ).…”
Section: Proteomics Technologies For the Identification Of Markersmentioning
confidence: 99%
“…In high-grade disease samples, SOX2 , TP63 and human gonadotrophin mRNAs were upregulated. Immunohistochemistry experiments performed revealed that SOX2 and TP63 proteins visibly outlined tumor cells in invasive forms of squamous cervical cancer ( 121 ).…”
Section: Proteomics Technologies For the Identification Of Markersmentioning
confidence: 99%
“…Изменения экспрессии клеточных белков Ki-67 [21,24,25], PCNA [26,27], p53 [21,28], p16(INK4a) [21,24,25,29], Bcl-2 [28], OCT-4 [30], COX-2 [24], SOX2, р63 [31] оказались более информативны в качестве дифференциальных признаков цервикальной неоплазии разной степени тяжести [21,29]. Их корреляция с тяжестью цитологических и(или) гистологических поражений [32] может быть обусловлена механизмом, не связанным с вирусным поражением клетки [33].…”
Section: Introductionunclassified
“…Stem cell associated proteins including human chorionic gonadotropin, the oncogene TP63 and the transcription factor SOX2 were upregulated in samples from women with CIN3 [55]. The stem cell related, cell surface protein podocalyxin was detectable on cells in samples from a subset of women with CIN3.…”
Section: Introductionmentioning
confidence: 99%
“…The stem cell related, cell surface protein podocalyxin was detectable on cells in samples from a subset of women with CIN3. SOX2 and TP63 proteins clearly delineated tumour cells in invasive squamous cervical cancer [55]. …”
Section: Introductionmentioning
confidence: 99%